Gagal Ginjal Akut Akibat Rabdomiolisis yang Diinduksi Status Epileptikus - Fahmi Ikhtiar; riskita fiannisa; evi kurniawati; ari wahyuni (CV. Jasa Sukses Abadi, 2021)
Status epilepticus is any type of epileptic seizure that fails to stop and lasts for more than 30 minutes. This condition is an emergency in the field of neurology. In adults, almost 50% of status epilepticus is caused by acute cerebrovascular disease, hypoxia, metabolic disorders, and inadequate epilepsy treatment. While in children caused by infection of the central nervous system, metabolic disorders, trauma, and anoxia. If the seizures do not stop and last for a long time, they can lead to complications such as rhabdomyolysis. Rhabdomyolysis is a syndrome that can be life-threatening due to the breakdown of skeletal muscle cells. Skeletal muscle cells release toxic substances such as myoglobin which will clog the tubules in the kidneys, interfere with urinary excretion, and cause acute renal failure. Diagnosis is based on clinical signs and symptoms, and laboratory tests. Early signs are non-specific. Symptoms may include muscle weakness, increased body temperature and local or generalized muscle pain. Laboratory tests are carried out to confirm the diagnosis, namely looking at the amount of creatine kinase. The incidence of acute renal failure due to rhabdomyolysis is around 10% - 40%. In addition, antiepileptic drugs such as phenytoin have been reported to have an association with acute kidney failure.